Engaging smallholder-farmers in model-based identification of alternative options, trade-offs and synergies for sustainable intensification in North-Tanzania - Kirimbo, G.E. (Wageningen University & Research, 2017)
Crop-livestock farming systems in Babati are under severe pressure from a fast growing human population. Continuing soil fertility degradation and the extinction of communal resources are linked to low crop yields and high poverty rates among the smallholder farmers. Alternative intensification options such as the use of improved seeds, phosphorus based fertilizers and manure in maize-pigeon pea intercrop and tomato as a new crop have been proposed by the Africa RISING project to improve farm productivity. The feasibility of these field level options needs to be assessed at farm-scale to give insight into the interactions between crops, soils, animals and the household. We used the farm-scale model, FarmDESIGN, to explore alternative options for differently resource endowed farms to enhance their farm performances in terms of economic, environmental and social indicators by combining the current farm resources with the AR interventions. Two sample farms of each farm type were selected. In addition, the study attempted to engage smallholder farmers and extension workers. Data for the current farms were obtained from a previous study while data for the novel interventions were gathered from literature reviews and ongoing research experiments. The windows of opportunities and the preferred innovations depended on available land sizes, current cropping systems and livestock ownership. The High Resource Endowed farms showed widest ranges of potential improvements in terms of operating profit followed by the Medium Resource Endowed farms while the Low Resource Endowed farms showed modest improvements. Improvements in terms of operating profit and soil organic matter were possible by reducing area under the currently grown crops and adopting the Africa RISING interventions. However, often strong trade-offs with household leisure time were evident due to the high labour demand of these inventions. Cultivation of the high value tomato crop with its characteristic low soil organic matter inputs created strong trade-offs between operating profit and organic matter balance. Adopting the new practices of maize-pigeon pea intercrop, maintaining or slightly increase animal numbers as well as incorporating a portion of the crop residues into the soil played a key roles in increasing organic matter balances on all farm types. The interactions with farmers allowed virtual experiential learning to take place and provided evidence that the farmers found the simulation outcomes credible and meaningful. We conclude that the model is an effective tool in exploring windows of opportunity within smallholder farming systems and promotes the discussion of future farm development options between smallholder farmers and extension workers.